Pentadbiran harta menurut Islam. (Kuala Lumpur Institut Kefahaman Islam, Malaysia, 1999)
Wealth and property according to Islamic law in Malaysia; papers of a seminar.
Includes bibliographical references (p. 282-284).
Keywords: Property (Islamic law) -- Malaysia -- Congresses; Property -- Malaysia -- Congresses; Wealth -- Religious aspects -- Islam -- Congresses; Wealth -- Malaysia -- Congresses